Degradation mechanism of lead-vanado-iodoapatite in NaCl solution. (1st August 2020) - Wang, Yachun; Yao, Tiankai; Xi, Fayuan; Lei, Penghui; Guo, Xiaolei; He, Lingfeng; Frankel, Gerald S.; Lian, Jie
Highlights: Higher Cl − concentrated solutions led to fast iodine release and deeper reaction zone in the IAPT matrix. Micron-sized Cl-bearing apatite crystals precipitated on the corroded surface eventually control the concentrations of Pb and V in bulk solution. Ultrafine Cl-bearing apatite crystallites formed in the alteration layer and a grain subdivision was observed. Both ion-exchange and interface coupled dissolution-reprecipitation mechanisms may play roles in determining the degradation behavior. Multiple complex phenomena occurred across the solid-liquid and solid-solid interfaces at different length scales. Abstract: Degradation mechanism of lead-vanado-iodoapatite (IAPT) in NaCl solution at 90 °C was investigated through systematic characterization of surface morphology, microstructure and microchemistry evolution of the alteration layer. Nano-scale characterization indicated that IAPT crystals degraded from grain boundaries toward inner grains, forming ultrafine Cl-bearing crystallites. A coupled interface dissolution-reprecipitation replacement mechanism and the ion exchange between Cl − and I − across the degradation zone may together play roles in determining the nano-scale degradation behavior of IAPT. This work highlights the degradation through multiple reactions and elemental transport across the liquid-solid and solid-solid interfaces at length scales from sub-millimeter to nanoscale.